A percepção ambiental como base para um sistema de indicadores dos serviços ecossistêmicos e ambientais de parques urbanos - Silva, Giulia Beatriz Mota da (2023)
The urban expansion model spread in Latin American countries, with the predominant use of gray infrastructure, suppression of green areas, and generation of pollution, causes the degradation of environmental quality, resulting in socio-environmental and economic damages that compromise the quality of life in cities. Given this context, there is a growing need for investment in environmental planning, in order to increase the resilience of these environments. The creation of green urban areas emerges as a key instrument for this purpose, because they provide health and quality of life for the population, through the promotion of environmental services (AS) and the recovery of essential ecosystem services (ES). Given the above, this work aimed to use the environmental perception to generate indicators of AS and ES in Parahyba 2 and Zoo Botanical Park Arruda Câmara, located in João Pessoa-PB. Initially, the methodology consisted of a literature review, followed by on-site visits and characterization of the study areas. Subsequently, a structured questionnaire was developed and applied via electronic means for assessing the environmental perception of park users, covering the sociodemographic characterization of participants and questions about the provisioning, regulation, habitat, and cultural services and about the structure and management of the sites; at this stage 250 interviews were conducted in each park. Finally, the data obtained were used for the development of the Index of Perception of Ecosystem and Environmental Services Provided by Urban Parks (IPSEAPU), and a classification for the perception of the provision of the services by parks was developed from the result of IPSEAPU. The results showed that the parks studied have distinct characteristics and objectives and are perceived by the park-goers also differently regarding the AS and ES provided. The study of environmental perception showed a low perception of the provisioning services in both parks. The habitat, regulation, and cultural services stood out; however, it was found a higher perception of these in the PZAC. The application of IPSEAPU provided results of 0.5997 and 0.6332, respectively, for PP2 and PZAC, which placed them in the intermediate category regarding the perception of provisioning of AS and ES. It can be concluded that IPSEAPU enabled the identification of current weaknesses in the perception of the local population regarding the provision of AS and ES, through individual indicators, and can serve as a starting point for the establishment of goals and strategies for environmental management. Furthermore, the methodology used in this research is fully adaptable and can be used in other categories of parks in different urban contexts.